Culinary Tourism Menu Variation in Mandalika Lombok through Pizza Making Innovation with the Addition of Coconut Oil - Kanom Kanom (Universitas Muhammadiyah Yogyakarta, 2023)
Mandalika Lombok is one of the super-priority tourism destinations in Indonesia. Culinary is one of the important elements needed by tourists, thus innovation and menu variations are needed. Pizza is one of the menus available at Mandalika Lombok, however, there are still not many variations. The availability of adequate and minimal use of Virgin Coconut Oil (VCO) is one of the considerations for making innovations, namely making pizza with the addition of Virgin coconut oil (VCO), as an alternative and a variety of culinary tourism menus in Mandalika Lombok. This study used a non-factorial randomized block design with organoleptic tests including hedonic quality tests and hedonic tests with concentrations of 0%, 50%, 75%, and 100%. The results of the analysis showed that the addition of Virgin coconut oil (VCO) had a significant effect on the Hedonic Quality Test (P0.05) and significantly affected the Hedonic Test (P0.05). The best treatment from the Hedonic Quality Test Results is T3 with a score of 4.20 and the best treatment in the Hedonic Test is T3 with a score of 4.46.